Studi Etnomatematika pada Ornamen dan Konstruksi Jembatan Musi VI sebagai Representasi Kearifan Lokal - Irfansyah, Hastin Nur; Arfinanti, Nurul (Universitas PGRI Semarang, 2026)
Ethnomathematics can create enjoyable and meaningful learning for students. Ethnomathematics not only improves understanding of mathematical concepts but also fosters a love for one's own culture. This study aims to explore the cultural elements and mathematical concepts found in the Musi VI Bridge. The research method used was qualitative research using a literature review, document study, observation, and interviews. The results of the analysis and discussion show that the Musi VI Bridge contains cultural and mathematical concepts known as ethnomathematics. Mathematical elements such as geometry, including isosceles triangles, circles, semicircles, squares, rectangles, and blocks, were found. In addition to mathematical elements, the Musi VI Bridge serves as a connector between the Seberang Ulu and Seberang Ilir areas in the city of Palembang.